Understanding The Relationship Between Faith and Knowledge - Philip Suciadi Chia; Juanda Juanda (Jurnal Didaskalia, 2020)
The issue of the relationship between faith and knowledge is very interesting to be studied from the contemporary times. Each period of life is unique in understanding the issues of faith and knowledge. Likewise, John Hick's opinion in his book ‘Faith and Knowledge’ is very interesting to be researched.In this brief paper, the writer limits the definitions analysis to Oxford Dictionary and John Hick. Then, the writer will evaluate those definitions to clarify the relationship between faith and knowledge. The understanding that opposes faith and knowledge will cause confusion when talking about the issue of them.Is there a gap between faith and knowledge? We would say that there is no gap between them. We admit, however, that there is a sequence or an order between them. First, it begins with the revelation of God that produces passive faith to us. Through various circumstances, experiences and education, we as human being will embrace the process of getting knowledge about reality and God’s revelation.